Aqua rooting of semi-hardwood grape cuttings: A rapid cloning technique for rootstocks - Meena, Sonam; Jogaiah, Satisha; Singh, Sanjay K.; Vincent, Linta; Jha, Anjani K. (Indian Horticulture, 2024)
Grape cultivation is highly remunerative when it is grown on recommended rootstocks. However, poor rooting and multiplication rate of recommended rootstocks pose serious problem in large scale replanting, covering new areas etc. Moreover, conventional methods pose problems due to spread of diseases and nematodes. Hence, grape rootstock propagation through semi-hardwood cutting in water cups is an efficient technique, which can produce healthy plantlets in bulk. It can be practiced multiple times in a year by effectively using the huge amount of thinned vine segments during pruning/grafting/training of vines.